PENINGKATAN HASIL BELAJAR IPA PADA MATERI LISTRIK DINAMIS MELALUI MODEL PEMBELAJARAN AKTIF TIPE TALKING STICK SISWA KELAS IX.2 MTSN 5 SOLOK SELATAN - FATIMAH FATIMAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Students The purpose of this classroom action research is to improve the science learning outcomes of class IX.2 students in Semester I at MTsN 5 Solok Selatan. This type of research is action research with two rounds. Each round goes through stages, namely: planning, implementation, data collection, and reflection. The research subjects were students of class IX.2 in Semester I at MTsN 5 Solok Selatan with 33 students and teachers in charge of these subjects. The data obtained in the form of formative test results and observation sheets of teaching and learning activities. From the results of classroom action research that has been carried out on class IX.2 students in Semester I at MTsN 5 Solok Selatan about the application of the Talking Stick learning model in the learning process IPA student class IX.2 in Semester at MTsN 5 Solok Selatan 2019/2020 academic year. So it can be concluded that learning achievement which is also a manifestation of student process skills in learning in class IX.2 students shows that from 33 students in the first cycle, 45% mastery increases in the second cycle to 88%. Based on the results of cycle I and cycle II, it can be concluded that the Talking Stick learning model can improve students' science learning outcomes. The application of the Talking Stick learning model can improve students' science learning outcomes. The number of students who achieved completeness in two cycles carried out in accordance with the KKM was determined by the achievement, which was 88%. ABSTRAKTujuan penelitian tindakan kelas ini adalah untuk meningkatkan hasil belajar IPA siswa kelas IX.2 pada Semester I di MTsN 5 Solok Selatan. Jenis penelitian ini adalah penelitian tindakan (action research) sebanyak dua putaran. Setiap putaran melalui tahap yaitu: perencanaan, pelaksanaan, pengumpulan data, dan refleksi. Subjek penelitian adalah siswa kelas IX.2 pada Semester I di MTsN 5 Solok Selatan dengan jumlah siswa 33 dan guru yang mengampu mata pelajaran tersebut. Data yang diperoleh berupa hasil tes formatif dan lembar observasi kegiatan belajar mengajar. Dari hasil penelitian tindakan kelas yang telah dilaksanakan pada siswa kelas IX.2 pada Semester I di MTsN 5 Solok Selatan tentang penerapan model pembelajaran Talking Stick dalam proses pelajaran IPA siawa kelas IX.2 pada Semester di MTsN 5 Solok Selatan Tahun Pelajaran 2019/2020. Maka dapat disimpulkan prestasi belajar yang juga merupakan perwujudan dari keterampilan proses siswa dalam belajar pada siswa kelas IX.2 menunjukkan dari 33 siswa pada siklus I ketuntansan 45% meningkat pada siklus II menjadi 88%. Berdasarkan hasil siklus I dan siklus II tersebut dapat disimpulkan bahwa model pembelajaran Talking Stick dapat meningkatkan hasil belajar IPA siswa. Penerapan model pembelajaran Talking Stick dapat meningkatkan hasil belajar IPA siswa. Jumlah siswa yang mencapai ketuntasan pada dua siklus yang dilaksanakan sesuai dengan KKM ditetapkan dengan pencapaian, yaitu 88%.